Analysis of social economy and policies on production management systems: a case study on China’s bamboo industry - Zhong Maogong; Fu Maoyi; Belcher, B.; Ruíz Pérez, M. (1997)
Over recent years, there has been rapid development of the bamboo industry in China since reform and liberalisation, which have brought about a series of economic policies and regulations favourable to economic development. Between 1981 and 1993, the area covered by bamboo forests expanded at a rate higher than the growth rate in forest-covered areas of the country over the same period. By 1996, the annual production value of primary products from bamboo resources reached 0.9 billion USD. The export value of manufactured bamboo products was US$ 35 million in 1995. Because 93% of bamboo forests in rural areas is collective-owned and directly managed by farmers, the increase in yields and profits from bamboo forest products significantly improves incomes and living standards of rural people. Thus the bamboo industry has become an important means to reduce poverty among the rural population. The purpose of this study is to promote sustainable development of the bamboo sector by reviewing the development of bamboo industries in Anji County, Zhejian Province. The review analyses industry fundamentals, approaches and potential weaknesses and explores the direction and methods for its further development.